2020
DOI: 10.13057/biodiv/d210862
|View full text |Cite
|
Sign up to set email alerts
|

The diversity, population, ecology and conservation status of waterbirds in the wetland of Bangpu Nature Education Center, Thailand

Abstract: Abstract. Chanate W, Wasan D, Pisarut Y, Rungtip S. 2020. The diversity, population, ecology, and conservation status of waterbirds in the wetland of Bangpu Nature Education Center, Thailand. Biodiversitas 21: 3910-3918. Wetlands are a crucial habitat for waterbirds as they provide feeding and breeding sites and increase survival rates during the non-breeding season. This study aimed to update the status of waterbirds in Bangpu Nature Education Center, Samut Prakarn Province, Thailand by evaluating the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is said that 10% of bird species out of the total global number depend on wetlands, and 20% use them to find food, rest, and breed (Rannestad et al 2015;Kačergytė et al 2021;Jangral and Vashishat 2022). In a study of bird diversity and populations in the wetlands of the Bangpu Nature Education Center, Thailand, it was recorded that eight families of water birds lived and used the wetlands, including Scolopacidae, Ardeidae, Charadriidae, Laridae, Ciconiidae, Phalacrocoracidae, Recurvirostridae, and Rallidae (Chanate et al 2020). In China, Luo et al's (2019) research in the Dianchi Lake wetlands revealed that 67 of the 182 bird species were water birds.…”
Section: Discussionmentioning
confidence: 99%
“…It is said that 10% of bird species out of the total global number depend on wetlands, and 20% use them to find food, rest, and breed (Rannestad et al 2015;Kačergytė et al 2021;Jangral and Vashishat 2022). In a study of bird diversity and populations in the wetlands of the Bangpu Nature Education Center, Thailand, it was recorded that eight families of water birds lived and used the wetlands, including Scolopacidae, Ardeidae, Charadriidae, Laridae, Ciconiidae, Phalacrocoracidae, Recurvirostridae, and Rallidae (Chanate et al 2020). In China, Luo et al's (2019) research in the Dianchi Lake wetlands revealed that 67 of the 182 bird species were water birds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been mentioned that wetland provides a unique habitat for many residential bird and migratory bird species (Zhijun, et al, 2010;Ghasemi, et al, 2012;Shao et al, 2014;Bhatt, 2015;Saini et al, 2017;Wanna et al, 2020. Some studies in India (Kaushik et al, 2013, Bhatt et al, 2015, Saini et al, 2017 have been reported wetland provides good shelter, food, and enhance the waterbird diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been mentioned that wetland provides a unique habitat for many residential bird and migratory bird species (Zhijun, et al, 2010;Ghasemi, et al, 2012;Shao et al, 2014;Bhatt, 2015;Saini et al, 2017;Arya et al, 2019;Wanna et al, 2020. Some studies in India (Kaushik et al, 2013, Bhatt et al, 2015, Saini et al, 2017, Arya et al, 2019 have been reported wetland provides good shelter, food, and enhance the waterbird diversity.…”
Section: Introductionmentioning
confidence: 99%